The role of alcohol use in HIV transmission among Grootfontein residents – Namibia - Kumwenda, Andrew (Stellenbosch : University of Stellenbosch, 2009)
Thesis (M.Phil. (Industrial Psychology))--University of Stellenbosch, 2009.